Pertumbuhan Dan Serapan Nitrogen Azolla microphylla Akibat Pemberianfosfat Dan Ketinggian Air Yang Berbeda - Putra Utama; Dewi Firnia; Ganes Natanael (Agrologia, 2015)
Water fern Azolla microphylla symbioses with Anabaena azollae which is able to fix N2. Fern growth is strongly influenced by the availability of macro nutrients such as phosphate. The aim of this study was to determine the effect of concentration of phosphate fertilizers and different water levels on the growth and nitrogen uptake of Azolla microphylla. Research was conducted by using randomized block design with three replications. The treatment were  water level which consists of 0 cm, 2 cm, 4 cm, and 6 cm, and the concentration of phosphates (P) which is composed of without and with  15 ppm, 30 ppm and 45 ppm. The results showed that the water level are interdependent with the phosphates concentration to influence  Azolla’s covered area at  7-21 days after planting, wet weight, total dry weight, and total nitrogen uptake of Azolla microphylla. The water level 2 cm at a concentration of 30 ppm of phosphate fertilizers is the best treatment combination to increase Azolla’s covered area at 7-21 HST, wet weight, total dry weight, and total nitrogen uptake of Azolla microphylla.